A rare case of deep vein thrombosis in upper extremity: a case report - Sheerazi, Mohammed Adnan; Khan, Furqan Mohd. Akram (International Journal of Research in Medical Sciences, 2020)
The incidence of deep vein thrombosis (DVT) in upper limb is less common as compared to lower extremities. There were no institutional screening protocols for patients at risk of DVT in upper limb. Hence this case report was presented to describe the features of upper limb DVT.